Recombinant expression of Streptococcus pneumoniae capsular polysaccharides in Escherichia coli. Issue 4 (April 2016) - Kay, Emily J.; Yates, Laura E.; Terra, Vanessa S.; Cuccui, Jon; Wren, Brendan W.
Abstract : Currently, Streptococcus pneumoniae is responsible for over 14 million cases of pneumonia worldwide annually, and over 1 million deaths, the majority of them children. The major determinant for pathogenesis is a polysaccharide capsule that is variable and is used to distinguish strains based on their serotype. The capsule forms the basis of the pneumococcal polysaccharide vaccine (PPV23) that contains purified capsular polysaccharide from 23 serotypes, and the pneumococcal conjugate vaccine (PCV13), containing 13 common serotypes conjugated to CRM197 (mutant diphtheria toxin). Purified capsule from S. pneumoniae is required for pneumococcal conjugate vaccine production, and costs can be prohibitively high, limiting accessibility of the vaccine in low-income countries. In this study, we demonstrate the recombinant expression of the capsule-encoding locus from four different serotypes of S. pneumoniae within Escherichia coli . Furthermore, we attempt to identify the minimum set of genes necessary to reliably and efficiently express these capsules heterologously. These E. coli strains could be used to produce a supply of S. pneumoniae serotype-specific capsules without the need to culture pathogenic bacteria. Additionally, these strains could be applied to synthetic glycobiological applications: recombinant vaccine production using E. coli outer membrane vesicles or coupling to proteins using protein glycan coupling technology.